Praziquantel is an effective drug for the treatment of Schistosoma Mansoni infection among school-aged children in Northwest Ethiopia - Tesfie, Addisu (Trop Med Health, 2020)
BACKGROUND: The appropriate drug for the treatment of schistosomiasis is praziquantel. However, low cure rate and existence of drug resistance both in vivo and in vitro were reported in different endemic areas. Hence, the aim of this study was to evaluate the effectiveness of praziquantel for Schistosoma mansoni (S. mansoni) treatment. METHODS: A cross-sectional study was conducted in Sanja General Primary School, North Gondar Zone, Amhara region, Northwest of Ethiopia, from March to April, 2017. A total of 245 participants were selected using systematic random sampling. A stool specimen was collected from each participant and examined for S. mansoni ova load count using Kato–Katz technique. Two hundred four infected participants were treated with a single oral dose of praziquantel 40 mg/kg. Four weeks later post-treatment, stool specimens were collected from 176 study participants. The samples were collected using similar procedures like the pre-treatment phase to see egg reduction and cure status. Data were entered and analyzed using SPSS version 20.0 Pearson chi-square (χ(2)) was used to determine the association of effectiveness of the drug with the average egg count, age group, and sex. P value ≤ 0.05 at 95% CI was considered statistically significant. RESULTS: Pre-treatment prevalence of S. mansoni infection was 83.3% (204/245) with geometric mean egg count of 357.8. In those not cured post-treatment, the prevalence and egg per gram in geometric mean egg count were 13.1% and 77.6 respectively. After 4 weeks of administration of praziquantel, the cure rate was 86.9% with egg reduction rate of 78.3%. Effectiveness of the drug was not statistically associated with sex, age group, and pre-treatment intensity of infection. CONCLUSION: S. mansoni prevalence was high. Praziquantel is an effective drug for the treatment of S. mansoni. This high prevalence of S. mansoni requires mass drug administration of praziquantel.